PENERAPAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR - Fitri Choirul Muttaqin; Serlia Novita Sari; Wahyu Nur Hidayati; Adi Nurcahyo; Artik; Edy Heru Prasetyo; Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Creativity is one of the key skills required in the 21st century. Based on observations conducted at SD Muhammadiyah Plus Malangjiwan, Colomadu, Karanganyar, Central Java, pupils’ creativity remains low due to the use of less appropriate learning models. Creativity helps pupils to develop meaningful and high-quality ideas. Therefore, teachers must be able to design learning experiences that can enhance pupils' creative thinking. One example of a learning model that can foster students’ creativity is Project Based Learning (PjBL). The aim of this study is to improve pupils’ creativity through the implementation of the Project Based Learning model. This research adopts a descriptive quantitative approach. The creativity assessment instrument is based on the framework developed by the OECD. Data analysis techniques used include the paired sample t-test and the N-gain test. The results show a difference between the pre-test and post-test scores. The N-gain test analysis yielded a score of 0.5, indicating a moderate increase in pupils’ creativity.